1996
DOI: 10.1046/j.1365-2567.1996.465550.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired immunity and altered pulmonary responses in mice with a disrupted interferon‐γ receptor gene exposed to the irradiated Schistosoma mansoni vaccine

Abstract: SUMMARYA high level of protection against Schistosoma mansoni is elicited in mice by the irradiated cercaria vaccine and interferon-g (IFN-g) is a key cytokine in the pulmonary effector response. The role of this cytokine has been investigated in mice with a targeted disruption of the IFN-g receptor gene (IFN-gR ÿ /ÿ mice). The level of protection was impaired relative to that elicited in C57BL/6 and 129 wild-type (WT) animals. These two groups developed compact effector foci, of largely mononuclear cell compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 38 publications
4
70
0
2
Order By: Relevance
“…Ϫ/Ϫ mice is significant because the absence of many other immune components (e.g., IFN-␥ [20], IFN-␥R [57], IL-4R␣ [35], and IL12p40 [2,16]) only leads to the partial abrogation of resistance. Our studies using CD154 Ϫ/Ϫ mice that do not produce anti- CD154 is important for optimal expression of MHC-II and CD86 by APCs in the skin and their migration from the skin to the sdLN (32), which are important in immune priming against schistosomes (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ϫ/Ϫ mice is significant because the absence of many other immune components (e.g., IFN-␥ [20], IFN-␥R [57], IL-4R␣ [35], and IL12p40 [2,16]) only leads to the partial abrogation of resistance. Our studies using CD154 Ϫ/Ϫ mice that do not produce anti- CD154 is important for optimal expression of MHC-II and CD86 by APCs in the skin and their migration from the skin to the sdLN (32), which are important in immune priming against schistosomes (24).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of antibodies in CD154 Ϫ/Ϫ mice has allowed us to examine the nature of the cell-mediated effector mechanism that was previously thought to be at least partially responsible for conferring protection (1,2,14,16,20,33,53,57,59,60). However, despite recreating the Th1-mediated immune responses in the lungs following the administration of IL-12, we were unable to recreate a protective response against challenge parasites, even to a limited extent.…”
Section: Discussionmentioning
confidence: 99%
“…The established dogma that protective immunity to a single dose of the RA schistosome vaccine in C57BL/6 mice is associated with a strong Th1 cell-mediated immune response involving an inflammatory reaction to challenge parasites in the lungs has been supported in many studies using cytokine ablation treatments (57,59) or cytokine-deficient mice (1,23,64). Therefore, we predicted that in the absence of IL-4R signaling, Th1-type responses would increase and that consequently protective immunity would be greater in IL-4R␣ Ϫ/Ϫ than in WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…They also indicate that Th2-type response may be detrimental for cysticercosis. Moreover, others using radiation-attenuated vaccine and IL-12 as an adjuvant against Schistosoma have shown that a Th1-like response can mediate protective immunity in this model (22,23).…”
Section: T Crassiceps-infected Stat6mentioning
confidence: 95%